Dental Care use and Self-Reported Dental Problems in Children in Lahore, Pakistan - Hazik B. Shahzad, Farhat Kazmi, Saadia Manzar, Shahrayne Rashid, Faiza Awais, Anas Imran Arshad, Sakeena Zahra, Mohammad Khan Ghafoor, Baneen Zahra, Shaleezay Rashid Khan, Wan Muhamad Amir W Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: Oral diseases affect a probable 90% of school children worldwide. Understanding the behaviours among children would give us the information required to create better health programmes. This cross-sectional research aims to assess oral health behaviours among school children. Methods: Data was collected using a WHO oral health questionnaire for children and 527 students participated from four schools in Lahore. Results: The research shows that in schools in Lahore, there are still 29.5% of students who are irregular in their brushing habits. The use of toothpaste was widespread although information on fluoride in toothpaste was limited. Students regularly took milk and tea with added sugar (43.9% and 49.2%). Fresh fruit consumption was 22%. According to regression analysis, females were 1.96 times more likely to be made fun of their teeth when compared to males. Higher parental education brought about significantly better brushing habits but also significantly higher odds for eating candies and sweets (1.29) and lower odds (0.57) for eating fresh fruits. High consumption of sugary foods was related to more dental visits. Practical implication & Conclusion: Self-assessed dental health is positive amongst the students in Lahore. However, this research indicates a significant portion of the students have irregular oral hygiene practices and sporadic dental visitation. Oral health education should be incorporated into the school environment with the support of teachers and parents so that it becomes a lifetime practice. Keywords: Child oral health, WHO oral health questionnaire, Fresh fruit consumption.